Optimizing vitamin A supplementation: A comparative cost-effectiveness analysis of routine distribution strategies in northern Côte d’Ivoire - Melissa M. Baker; Lyonel Nerolin Doffou Assalé; David Doledec; Romance Dissieka; Ahmenan Claude Liliane Konan; Agnes Helen Epse Assagou Mobio; Koffi Landry Kouadio; Oka René Kouamé; Ama Emilienne Yao; Hubert Zirimwabagabo (PLoS ONE, 2025)
Background While recent data on vitamin A deficiency (VAD) prevalence is lacking, the 2004 Côte d’Ivoire Nutrition and Mortality Survey reported that 26.7% of children aged 6–59 months were affected by VAD, and approximately 60% were at risk. Since 2016, the government has transitioned from mass campaigns to routine vitamin A supplementation (VAS) delivery integrated into health services. However, evidence on the cost-effectiveness of the routine distribution approaches is limited. This study evaluated the cost, coverage, and cost-effectiveness of three routine VAS delivery strategies across two health districts in northern Côte d’Ivoire. Methods A mixed-methods study evaluated three routine VAS delivery strategies – routine-fixed, advanced community-based, and catch-up – across two health districts, Ferkessédougou and Niakaramadougou, in northern Côte d’Ivoire. The quantitative cost data were collected via a structured tool covering six cost categories: planning, procurement, training, social mobilization, distribution, and supervision. VAS coverage was assessed through a post-event coverage survey (PECS) via a two-stage cluster sampling methodology. A cost-effectiveness analysis determined the cost per child supplemented, the cost per DALY averted, and a sensitivity analysis tested the robustness of the findings under different cost scenarios. Results The total program cost for July-December 2023 was 25.5 million FCFA, with personnel costs comprising over 70% of expenditures. In Ferkessédougou, the routine advanced community-based strategy was the most cost-effective, at 458 FCFA per child in rural areas (versus 596 FCFA for the routine-fixed facility-based approach in the same area). In Niakaramadougou, the December catch-up was more cost-effective in rural areas (606 FCFA per child) than the routine-fixed approach (714 FCFA). Across both districts combined, the routine-fixed strategy averaged roughly 651 FCFA per child supplemented, and the cost per DALY averted ranged from 30,093 FCFA (advanced strategy in Ferkessédougou) to 89,550 FCFA (catch-up Jul 2023 in Niakaramadougou) – all below Côte d’Ivoire’s cost-effectiveness threshold (0.5 x GDP per capita; approximately USD 1,265). Conclusion All three strategies were cost-effective, though the advanced community-based strategy achieved the best balance of reach and efficiency. Scaling advanced strategies within health system constraints may enhance sustainability and coverage in low-resource settings.